Alternative Conceptions in Physics among Secondary School Students - Krishnan, Dhanya (JOURNAL OF INDIAN EDUCATION, 2017)
Considering the explorative nature of Physics and its intricate disciplinary characteristics, science educationists were always curious to explore how children learn Physics. It is a well-acknowledged fact that concept acquisition is a very active process wherein learners identify essential attributes and construct new conception integrating with already built conceptions in the mind. During the process of acquisition of concepts, learners may view the world in the form of concepts which are deviant from accepted notion of knowledge which are termed as alternative conceptions. If the alternative conceptions are not dealt at the secondary level, the probability of sustaining those alternative frameworks of conceptions may continue at higher learning too. This research paper attempts to identify alternative conceptions in Physics among secondary school students of D.M. School of Regional Institute of Education (RIE), Bhubaneswar, Odisha. All 9th standard students of D.M. School were considered as the sample. A two-tier concept attainment test and a semi-structured interview were used to collect the data. The data was qualitatively analysed with specific intention to explore students’ alternative conceptions in the themes—Motion, Force, Sound, Light and Electricity. The findings suggest that a well-constructed system of pedagogical design is to be integrated in the teaching-learning process so that alternative conceptions in Physics could be redirected to conceptual change among learners.